Use of water from air conditioning appliances in public building in the state of Pernambuco (Research, Society and Development, 2021)
Over the years with the irrational use of water, there is a need to rethik the ways in which water resources are used, adopting sustainable practices that aim to guarantee the future of new generations to come. Ways to migitate impacts can be reuse and water use, which includes the use of water from air conditioning units. This work aims to evaluate the feasibility of using water from the air conditioning equipment of Pharmaceutical Laboratory of Pernambuco (LAFEPE). Thus, the LAFEPE solid waste buildin 1 was taken as the object of study, which has 10 Fancoil type appliances with a total capacity of 310,50 TR (refriferation ton). The measurements were made directly in the drains of the equipment, in measurements of 2 minutes. The results achieved demonstrated that it is feasible to use this water, considering that a volumo f 223,18 m³/month was obtained. This volume supplies 100% of the non-potable demand for Garden irrigation. LAFEPE does not use water from the concessionaire, so the use does not bring direct financial savings, but points to environmental benefits that in the future will make all the diference.